Defining the Value of Health Technologies in Latin America: Developments in Value Frameworks to Inform the Allocation of Healthcare Resources. (2019) - Pichon-Riviere, Andres; Garcia-Marti, Sebastian; Oortwijn, Wija; Augustovski, Federico; Sampietro-Colom, Laura
Abstract: Objectives: The recent development of value frameworks to inform healthcare resource allocation responds to a demand to make the decision-making process more inclusive and explicit. The objectives of the 2018 Latin American (LAtam) Health Technology Assessment International (HTAi) Policy Forum were to explore the current international experiences and to discuss the potential application of value frameworks in Latin America. Methods: A background paper, presentations, and group discussions of Policy Forum members (43 participants, 12 LAtam countries represented) at the 2018 HTAi Policy Forum meeting informed this paper. Results: Participants agreed that HTA and decision making based on more comprehensive and inclusive value frameworks could improve health system effectiveness, efficiency, sustainability, and equity; promote transparency in the decision process; sustain a more comprehensive assessment of technologies; and facilitate stakeholder participation as well as accountability of decisions. Criteria that were identified as essential to be included in a value framework for LAtam were burden of illness and severity of the disease, effectiveness and safety of the technology, quality of the evidence, cost-effectiveness, and budget impact. Potential challenges identified for the application of value frameworks in LAtam, included scarcity of human resources and delays in the assessment process. Conclusions: Forum participants agreed that the next steps should be to identify appropriate processes and methodologies, adapted to the context of each country, regarding the application of value frameworks to improve the link between HTA and decision making.